Role of the fourth membrane domain of the NR2B subunit in the assembly of the NMDA receptor - Horak, Martin (2008)
N-methyl-D-aspartate (NMDA) receptors play crucial roles in excitatory synaptic transmission as well as in excitotoxicity. A growing body of evidence suggests that the regulation of both subunit composition and the number of NMDA receptors reaching the surface membrane are tightly regulated. Recently, we have shown that the third membrane domains (M3) of both NR1 and NR2B subunits contain endoplasmic reticulum (ER) retention signals that prevent the unassembled subunits from leaving the ER. Furthermore, these membrane domains together with NR1 M4 are necessary for negating the ER retention signals found in M3 of NR1 and NR2B. In this addendum, we present new electrophysiological data showing that mutation of the HLFY motif, located immediately after M4 of the NR2B subunit, abolishes the surface trafficking of full-length NR1/NR2B complexes (supporting previous immunofluorescent experiments from our lab); however, the deletion of the NR2B C-terminus including the HLFY motif did not affect the formation of functional receptors when two pieces of the NR2B subunit, NR2B truncated before M4 and NR2B M4, were co-expressed together with the NR1 subunit. These observations will help to uncover the processes involved in the assembly of NR1 and NR2 subunits into functional NMDA receptors.